2016
DOI: 10.1186/s12958-016-0153-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 17β-estradiol (E2) role in the regulation of corpus luteum function in pregnant rats: Involvement of IGFBP5 in the E2-mediated actions

Abstract: BackgroundIn several species, considerably higher levels of estradiol-17 (E2) are synthesized in the CL. E2 has been suggested to participate in the regulation of luteal steroidogenesis and luteal cell morphology. In pregnant rats, several experiments have been carried out to examine the effects of inhibition of luteal E2 synthesis on CL structure and function.MethodsDuring days 12–15 of pregnancy in rats, luteal E2 was inhibited by way of daily oral administration of anastrozole (AI), a selective non-steroida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our present results therefore suggest that the low expression of aromatase in the ovary could be related to the small size of large tertiary follicles (antral follicles). Likewise, this low aromatase expression in antral follicles of hypothyroid animals could be related to modifications in the formation and function of the corpus luteum [30], rather than changes in the folliculogenesis [31]. In this regard, hypothyroidism affects the proliferation, angiogenesis, and apoptosis in the corpus luteum of rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our present results therefore suggest that the low expression of aromatase in the ovary could be related to the small size of large tertiary follicles (antral follicles). Likewise, this low aromatase expression in antral follicles of hypothyroid animals could be related to modifications in the formation and function of the corpus luteum [30], rather than changes in the folliculogenesis [31]. In this regard, hypothyroidism affects the proliferation, angiogenesis, and apoptosis in the corpus luteum of rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, effects of oestrogens in the CL appear to vary among different species, depending on their concentration and local availability. Thus, for example, in the rat and rabbit, oestrogens have luteotropic potential, whereas exogenous administration of oestrogens in rhesus monkeys shortens luteal life span (Hassani et al., 1978 ; Karsc & Sutton, 1976 ; Miller & Keyes, 1978 ; Townson et al., 1996 ; Tripathy et al., 2016 ). In the guinea pig, E2 effects appear to be time‐dependent, as administration of oestrogens in early dioestrus induces uterus‐mediated luteolysis, while application after day 9 of dioestrus prolongs luteal function (Illingworth & Perry, 1973 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of igfbp-5a was signi cantly increased after overexpression of E2 in tongue sole, and PPI analyses showed that igfbp-5a was associated with dimorphism-related gene such as pappalysin-1 (X. H. . Tripathy (Tripathy et al, 2016) proposed that igfbp-5 may be one of the response genes to E2, and that inhibiting E2 content resulted in increased levels of igfbp-5 and reduced activation of igf1r, which led to reduced activation of PI3K and pAkt/PKB levels and inhibited growth.…”
Section: Introductionmentioning
confidence: 99%